Analysis of Lexical and Grammatical Meaning in the Song “Alamak” by Rizky Febian (Semantic Study) - Sulastri, Saptiana; Ayu, Centika; Anisa, Elegia; Uri, Marsiana; Hairatunisa, Syarifah (Bahasa Indonesia Prima, 2026)
Semantics is a branch of linguistics that studies the meanings and relationships among language units, such as words, phrases, clauses, and sentences. This study aims to analyze the lexical and grammatical meanings in the lyrics of the song